Biologic and small molecule therapies for psoriasis in individuals with Down syndrome: Two cases and a systematic review - Michal Moshkovich; Jonah W. Perlmutter; Ronald Vender (SAGE Open Medical Case Reports)
Down syndrome (DS), also known as trisomy 21, is a genetic condition linked to a higher prevalence of skin disorders, including psoriasis, which affects up to 8% of individuals. DS patients with psoriasis present unique management considerations, including a theoretical increased risk of infectious complications with immunosuppressive therapies. This report includes two cases and a systematic review summarizing available evidence on psoriasis characteristics and treatment outcomes in individuals with DS. We report two DS patients with psoriasis demonstrating variable therapeutic responses: one controlled with acitretin and another requiring secukinumab after multiple treatment failures. To contextualize these findings, we conducted a systematic review following PRISMA guidelines, identifying 10 studies comprising 37 DS patients with psoriasis. Methotrexate was the most frequently failed therapy. Biologics targeting IL-17 and IL-23 pathways achieved the highest rates of complete resolution. These findings reflect Th1/Th17-driven inflammation in DS and highlight the need for individualized, pathway-specific management strategies.